Necessary and inherent limits to internet surveillance - Joss Wright (Internet Policy Review, 2013)
Information technologies now play a huge role in both personal and institutional life, playing the role of a global communications medium. As our means of interaction increasingly centre on the internet, there is a desire from nation states to exercise control and obtain access to the communications of citizens. The stated reasons for this access and control are to prevent or investigate crimes, and to protect national security. This article argues that mass untargeted surveillance of internet-based communications is an excessive tool with respect to its potential for abuse against both society and individuals, and that its ability to prevent crime or terrorism are limited. By looking at existing technologies and example cases where surveillance has been applied, this article demonstrates that there are both inherent mathematical and technical limits to the potential for surveillance to achieve broad-scale prevention of crime and terrorism. In addition, the potential of surveillance to result in real harm to society necessarily places severe limits on how this technique should be applied in a free and democratic society.
Keywords: 300; Surveillance; Intelligence services; Base rate fallacy; Interception; Fundamental principles; Predictive algorithms; Privacy; Security; Content data; Communications data; Bundestrojaner; National Security Agency (NSA); PRISM; Tempora; Encryption; Liability; Transparency; Cyber security; Content; Censorship; Filtering